INFLUENCE OF AMYLOSE STARCH ON DEVELOPMENT AND LIFESPAN OF FRUIT FLY DROSOPHILA MELANOGASTER - Oleksandra Abrat (Vasyl Stefanyk Precarpathian National University, 2015)
Last years, the concept of resistant starch (RS) has evoked a new interest in researchers in the context of bioavailability of starch and its use as a source of dietary fiber. Based on clinical and animal research, RS has been proposed to be the most potentially beneficial starch fraction for human health. In this study, the effects of amylose starch as a fraction of RS on development and lifespan of fruit fly Drosophila melanogaster were investigated. In both Canton S and w1118 strains, the diet with 20% amylose RS delayed fly development, increased triacylglyceride level in the body of adult insects and reduced their lifespan compared to the diet with 4% amylose starch. Thus, our data clearly demonstrate that amylose starch at high concentrations may negatively affect fruit fly.